Exploration of Gender-Specific Authorship Disparities in the Pain Medicine Literature. Issue 1 (2nd November 2019) - Karri, Jay; Navarro, Sergio M; Duong, Anne; Tang, Tuan; Abd-Elsayed, Alaa
Abstract : Background: Given the readily increasing membership of the pain physician community, efforts toward correcting notable gender disparities are instrumental. The under-representation of women is particularly prevalent within leadership roles in academic medicine, thought to be driven largely by diminished research efforts. Consequently, we aimed to characterize gender differences among the highest impact pain literature. Methods: The 20 highest cited articles per year from 2014 to 2018 were extracted from each of seven impactful journals affiliated to the largest pain medicine societies. Collected data from each article included genders of the first and last authors, the number of citations accumulated and the journal impact factor at the time of publication. Results: Across all considered literature, female authors were surprisingly not under-represented when considering the national prevalence of female pain physicians. However, more in-depth analysis found trends toward significance to suggest that female authorship was relatively diminished within more impactful and higher cited literature. When exploring gender–gender collaboration patterns, we found that male authors were favored over female counterparts with statistical significance; it must be noted that this likelihood analysis and preference toward male authors may be statistically obfuscated by the high prevalence of male authors. Nonetheless, these findings help to quantify overt, demonstrated disparity patterns. Of note, this inequity may also be fully secondary to the lower number of female pain physicians and/or those involved in research endeavors and decreased number of submissions from female physicians. Establishing gender discrimination patterns as causal factors in such disparities can be extremely challenging to determine. Conclusion: In our analysis of authorship between genders within the context of pain medicine literature, we found trends, although non-significant, toward women being lesser represented in the more impactful literature. We suggest that these inequities are possibly resultant of a markedly small and outnumbered female pain physician membership that has yet to achieve a critical mass and possible implicit gender biases that may restrict female authorship. However, further exploration and analysis of this issue are necessary to more clearly illuminate which systemic deficits exist and how they may, in turn, be corrected with cultural and macroscopic organizational-driven change.